Auditoria regular de la institución educativa Instituto Libre de Circasia Quindío vigencia 2011 (2012)
This paper contains an audit Regular on the Free Educational Institution of the Municipality of Circasia Quindío by the Comptroller General of Quindío as control and monitoring body, the process focuses on the audit and budget of the Educational Institution; this activity is due to the increasing need for control in educational institutions, which seeks to ensure the proper use and management of public assets and resources.